The Impact of Sugarcane Plantations on the Socio-Economic Life of the Community in Sungai Asam Village, Kerinci Regency (2000–2023) - Juningsih, Putri; Asnan, Gusti; Anatona, Anatona (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This article discusses the Impact of Sugarcane Plantations on the Socio-Economic Life of the Community in Sungai Asam Village, Kerinci Regency 2000-2023. This article was written to analyze the Development of Sugarcane Plantations in Sungai Asam Village in 2000-2023 and its Impact on the socio-economic life of the community. This article uses a socio-economic history approach and uses the theory of agricultural involution developed by Clifford Geertz as an analytical tool to explain the subject matter. Then to analyze the problems in this thesis, historical research methods are used, namely heuristics, source criticism, interpretation and historiography. The results of this study indicate that sugarcane plantations as the economy of the community in Sungai Asam Village and are the largest sugarcane plantations in Kerinci Regency, but have not been able to provide welfare for the lives of sugarcane farmers. The welfare of farmers depends on fluctuations in the price of sugarcane. This then creates the dynamics of farmers' lives in the community which is reflected in the level of community consumption.